The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1991
DOI: 10.1002/mpo.2950190603
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction following treatment for childhood leukemia: A population‐based prospective cohort study of fertility and offspring

Abstract: Of all children diagnosed with leukemia in Denmark, Finland, Iceland, Norway, and Sweden, 981 had discontinued therapy before 1985 and had been followed up annually after cessation of therapy. Progeny was registered and fertility evaluated among survivors who passed age 18 years without a relapse (n = 299). By April 1989, 48 offspring were registered, one of whom had congenital anomalies. This was no more than expected from the incidence of birth defects in the general population. No childhood malignancies or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
45
1
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 46 publications
(28 reference statements)
7
45
1
1
Order By: Relevance
“…Thus, differences across diagnoses may become more apparent with increasing age. The findings in this report are in concordance with many studies [5,[55][56][57][58] even though others have not shown any difference between survivors and controls [7,12,36].…”
Section: Discussionsupporting
confidence: 95%
“…Thus, differences across diagnoses may become more apparent with increasing age. The findings in this report are in concordance with many studies [5,[55][56][57][58] even though others have not shown any difference between survivors and controls [7,12,36].…”
Section: Discussionsupporting
confidence: 95%
“…For statistical analyses some variables were grouped as follows: diagnoses: 1) leukemias (n ϭ 81), b) lymphomas (n ϭ 47), c) tumors of the central nervous system (CNS) (n ϭ 24) and d) other malignant solid tumors (n ϭ 55); surgery groups: a) no surgery or biopsy only (n ϭ 106), b) mutilating or extractive surgery (n ϭ 57) (amputation [8], osteotomy [3], brain surgery [22], splenectomy [9], and nephrectomy [15]), and c) others (n ϭ 44); other sequelae: a) no other sequelae (n ϭ 156), b) limb deformities (n ϭ 18) (amputation [8], caput necrosis of femur [2], growth delay of a limb [6], and paresis of a limb [2]) and c) other single sequelae (n ϭ 33) (impairment of vision [3], hearing [1], or balance [2]; epilepsy [3]; developmental impairment [4]; problems with heart [2], lung [2], bowel [2], or bladder [1]; functionally harmful cicatrices [3]; alopecia [1], secondary malignancies [2], thrombocytopenia [1], and delayed puberty [6]). …”
Section: Methodsmentioning
confidence: 99%
“…In two register-based studies of 299 and 409 young adults treated for ALL, a normal fertility rate and no excess of malformations were found [27, 28]. No evidence of increased risk of cancer in the offspring has been documented [29].…”
Section: Therapymentioning
confidence: 99%